ANALISIS KADAR AMONIA (NH3) DALAM AIR DI SUNGAI CILEUNGSI - Azizah, Mia; Humairoh, Mira (Universitas Nusa Bangsa, 2015)
The increasing number of their activities and industry, have caused the changes on the quality of the water .Research aimed at determined ammonia in the waters of the cileungsi with the methods non standard salycilate test kit of the spectrophotometer uv-visible with reference method fenat based on sni 06-6989.30-2005 .Research carried out with the methods purposive sampling , the sample of the water drawn represent part upstream , central and hilir the river cileungis .The results of the analysis and testing in the laboratory , ammonia levels in a stream cileungsi be between 0,160-0,460 mg / l and consequently qualified of quality standard pp no. 82 2001.